A simple and rapid transformation of golden apple snail (pomacea canaliculata) shells to calcium carbonate, monocalcium and tricalcium phosphates - Seesanong, S.; Laosinwattana, C.; Chaiseeda, K.; Boonchom, B. (My University, 2019)
This study was designed to manage golden apple snail shells, the wastes created in large amount daily from the consumption of the meat of golden apple snail (Pomacea canaliculata) shells by transforming them to advanced compounds; calcium carbonate (CaCO3), monocalcium phosphate monohydrate [Ca(H2PO4)2·H2O], and tricalcium phosphate [Ca3(PO4)2]. They were successfully prepared by a rapid, simple, environmentally benign method using easily available and low-cost instrument. All synthesized samples were characterized by X-ray fluorescence, X-ray powder diffraction, FTIR spectroscopy and scanning electron microscopy to confirm the identities with the standard materials. The reproducibility and low-cost method suggest that it could be used in industry for a large-scale production of calcium carbonate, monocalcium phosphate monohydrate and tricalcium phosphate from golden apple snail shells as a replacement of natural mineral resources and be a good way to manage these shell wastes.
Keywords: Calcium carbonate; Golden apple snail shell; Monocalcium phosphate monohydrate; P. canaliculata; Tricalcium phosphate